Pengaruh Intensitas Pencahayaan terhadap Kenyamanan Visual Pemustaka di Perpustakaan Universitas Metamedia - Rana Madhani Putri Zalmi; Gustina Erlianti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The purpose of this study was to determine the effect of room lighting intensity on the visual comfort of users in the Metamedia University library. This study is a type of quantitative research with a descriptive method. Data were obtained through distributing questionnaires at the Metamedia University Library. The population in this study were all students of Metamedia University totaling 1000 people. The sampling technique used simple random sampling with a sample size of 100 respondents. The data collection technique was carried out by distributing questionnaires to the research sample. In this study, the data analysis technique used quantitative statistics. Based on the results of the data analysis, this study obtained the results that there was an influence between natural and artificial lighting on the visual comfort of users in the Metamedia University library.